Affordances of School Ground Environments for Physical Activity: A Case Study on 10- and 12-Year-Old Children in a Norwegian Primary School - Kjønniksen, Lise; Wiium, Nora; Fjørtoft, Ingunn (Frontiers in Public Health, 2022)
Few studies have focused on how different school ground environments can stimulate physical activity (PA) in children. This study aimed at investigating the contributions of two school ground environments (a constructed schoolyard and a natural forest) on moderate to vigorous physical activity (MVPA) among Norwegian schoolchildren in 5th and 7th grades (28 boys, 24 girls). The current study described the two school ground environments that provided large (a total area of 95 m2 per child) and multifunctional spaces, giving the children several affordances for being physically active during the school day. The constructed schoolyard afforded a space of 44 m2 per child, with access to sports and game courts and varied equipment for PA. The natural forest provided a space of 50.6m2 per child for activities that afforded a wide range of PA. The two different environments contributed equally to MVPA in the children. The results indicated small differences across grades and gender, where boys, especially those in grade 5 spent more time in MVPA in the constructed schoolyard. If replicated in larger representative samples, the findings can inform policies and programs that aim at promoting recommended levels of PA among children using school outdoor environments and consequently, have some implications for the physical and mental health of schoolchildren during the current pandemic.